2020
DOI: 10.3390/ijerph17041210
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Fluctuation of Polycyclic Aromatic Hydrocarbons and Aerosol Genotoxicity in Long-Range Transported Air Mass Observed at the Western End of Japan

Abstract: In order to clarify the level transboundary air pollution caused by polycyclic aromatic hydrocarbons (PAHs) and genotoxic substances, aerosols were collected from forest and suburban sites in Nagasaki, west Japan, for 6 years. The PAH concentration was measured, and the genotoxicity of the substances were evaluated using the umu test. The results showed no notable trends in the concentration or toxicity of either sites throughout the study period. The suburban and forest sites shared similar seasonal fluctuati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 74 publications
5
5
0
Order By: Relevance
“…As in spring, advection from the northwest of Nagasaki was common in autumn, while advection from directions other than the northwest was increasing compared to winter. These results were almost the same as those of the previous study [19].…”
Section: Back Trajectory Analysissupporting
confidence: 92%
See 2 more Smart Citations
“…As in spring, advection from the northwest of Nagasaki was common in autumn, while advection from directions other than the northwest was increasing compared to winter. These results were almost the same as those of the previous study [19].…”
Section: Back Trajectory Analysissupporting
confidence: 92%
“…If PAH concentrations in the atmosphere are measured over long duration at Japanese sites that are directly exposed to transboundary pollution from China, the causal relationship between economic activities in China and PAH concentrations in Japan could be determined by tracing behaviors in the measured values. Our previous research showed no notable trends in PAH concentrations in Nagasaki, located at the west end of Japan, from 2012 to 2018 [19]. The purpose of this study was to identify recent behaviors in PAH concentrations in Nagasaki following the previous study and to speculate on the causes of these behaviors.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Long-range transported (LRT) air pollution indicates the atmospheric movement of pollutants for more than 100 km, affecting neighboring countries' air quality across national boundaries. It is well known that Japan has suffered from LRT air pollution such as Asian dust (AD) and acid rain from the Asian continent [1][2][3][4][5]. However, different patterns of LRT may vary air pollutant concentrations in monitoring areas.…”
Section: Introductionmentioning
confidence: 99%
“…However, rarely studies have combined these to generate a more holistic understanding that can help identify health risk areas, influencing factors, pollution trends, and the efficacy (or lack thereof) of policy interventions 11 . For instance, in Nagasaki Prefecture, most of the studies have only focused on either the health impact caused by air pollutants [14][15][16] , the long-range transport of air pollutants from the Asian continent [17][18][19] , or the effects of climatic variables and the spatial and temporal distribution of PM 2.5 20 . Although these studies provide essential information, a multi-method approach is necessary to understand better the distribution, factors, and current and future trends of PM 2.5 and NO 2 pollution in Nagasaki Prefecture.This study used a multi-method approach to analyze PM 2.5 and NO 2 data in Nagasaki Prefecture from 2013 to 2021.…”
mentioning
confidence: 99%